IMPLEMENTASI KEGIATAN EKSTRAKURIKULER PRAMUKA DALAM MEMBENTUK KESADARAN BERBANGSA DAN BERNEGARA PADA SISWA KELAS V SEKOLAH DASAR - Zahra Meyliana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of Scout extracurricular activities in shaping national and state awareness among fifth-grade students at SDN Cipinang Muara 20 Pagi. This research uses a qualitative approach with a descriptive method. Data collection techniques include observation, interviews, and documentation. The results show that Scout activities can instill awareness of national identity, unity, tolerance, rule obedience, patriotism, and understanding of rights and obligations as citizens. Despite facing obstacles such as low student motivation and time constraints, these activities demonstrate a positive impact on students’ character development. Therefore, Scouting is an effective means of instilling national values from an early age in elementary schools.